Intellectual Property in Pharmaceutical Industry - Pospíšil, Kristián (2016)
The aim of the thesis is to analyze the modes of protection of pharmaceutical patents in an international trade from the viewpoint of both research oriented pharmaceutical and generic pharmaceutical company. More specifically, what are the steps needed to ensure the protection of a pharmaceutical in an international environment. Secondly, it is scrutinised what economic benefits such protection has and how it may impact the developing countries as the patent provides the patent owner with monopoly that lies in the exclusive time-bound production of the medicament. Thirdly, it is examined how the International community and organizations cope with the protection of pharmaceutical patents if such protection brings about negative effects on public health.